Social Inequalities in Student Employment and the Local Labour Market - Marita Jacob; Maria Gerth; Felix Weiss (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
This article examines class-specific employment patterns among students in Germany, taking into account how different local labour market conditions affect the quantity and quality of jobs available to students. We argue that the availability of jobs affects social inequalities in student employment. In particular, we expect a~stronger correlation between, on the one hand, the rate and quality of student employment and, on the other hand, students' socioeconomic background in towns with a~large pool of student labour, due to more competition for (good) jobs. Analysing data from German student surveys, we find that employment rates do not differ by social class background, but there are differences in the quality of their employment in terms of the fit between the job and the field of study. While we find that local labour market conditions affect student employment at a~general level, in contrast to our expectation, tighter labour market conditions seem to involve little or no disadvantage for students from less privileged social backgrounds.
Keywords: 300; Higher education; Student jobs; Social origin; Labour market; Educational inequality; Hochschulbildung; Studierendenerwerbstätigkeit; Soziale Herkunft; Arbeitsmarkt; Bildungsungleichheit